Do Community Free-Medication Service Policy Improve Patient Medication Adherence? A Cross-Sectional Study of Patients With Severe Mental Disorders in Beijing Community - Zhu, Junli; Huang, Qingzhi; Lu, Wei; Chen, Yun; Li, Bin; Xu, Ying; Xi, Rui; Li, Dan (Frontiers in Public Health, 2021)
Background: Nowadays, mental health problems have become a major concern affecting economic and social development, with severe mental health disorders being the top priority. In 2013, Beijing began to implement the Community Free-Medication Service policy (CFMS). This article aims to evaluate the effect of the policy on medication adherence. Methods: In this study, multi-stage sampling was used to select representative patients as samples. Some of the baseline data were obtained by consulting the archives, and information about patient medication adherence measured by Brooks Medication Adherence Scale was obtained through face-to-face interviews. Logistic regression was used to examine the impact of the policy. Results: Policy participation had a significant positive impact on medication adherence (OR=1.557). The effect of policy participation on medication adherence in the Medication-only mode and Subsidy-only mode were highly significant, but it was not significant in the Mixed mode. Conclusion: This study found that the CFMS in Beijing as an intervention is effective in improving the medication adherence of community patients. However, the impact of the policy is not consistent among service modes. Reinforcement magnitude and frequency should be considered when designing reinforcement interventions.